Differential Exposure to Job Stressors: A Comparative Analysis Between Migrant and Australia-Born Workers. Issue 9 (17th October 2019) - Liu, Xiaomin; Bowe, Steven J; Milner, Allison; Li, Lin; Too, Lay San; Lamontagne, Anthony D
Abstract: Aims: Previous studies have suggested that migrants have higher exposures to psychosocial job stressors than native-born workers. We explored migrant status-related differences in skill discretion/job complexity and decision authority, and whether the differences varied by gender, age, and educational attainment. Methods: Data were from Wave 14 of the Household Income and Labour Dynamics in Australia (HILDA) Survey. A total number of 9031 persons were included in the analysis. Outcomes included skill discretion/job complexity and decision authority. Exposure included migrant status defined by (i) country of birth (COB), (ii) the combination of COB and English/Non-English dominant language of COB, and (iii) the combination of COB and years since arrival in Australia. Data were analysed using linear regression, adjusting for gender, age, and educational attainment. These covariates were also analysed as effect modifiers of the relationship between migrant status and job stressor exposure. Results: In the unadjusted analysis, only migrant workers from Non-English-speaking countries (Non-ESC-born) had significantly lower skill discretion and job complexity than Australia-born workers (−0.29, 95% CI: −0.56; −0.01); however, results from fully adjusted models showed that all migrant groups, except migrant workers from Main-English-speaking countries, had significantly lower skill discretion and job complexity than Australia-born workers (overseas-born workers, −0.59, 95% CI: −0.79; −0.38; Non-ESC-born, −1.01, 95% CI: −1.27; −0.75; migrant workers who had arrived ≤5 years ago, −1.33, 95% CI: −1.94; −0.72; arrived 6–10 years ago, −0.92, 95% CI: −1.46; −0.39; and arrived ≥11 years ago, −0.45, 95% CI: −0.67; −0.22). On the contrary, the unadjusted model showed that migrant workers had higher decision authority than Australia-born workers, whereas in the fully adjusted model, no difference in decision authority was found between migrant workers and Australia-born workers. Effect modification results showed that as educational attainment increased, differences in skill discretion and job complexity between Australia-born workers and Non-ESC-born migrants progressively increased; whereas Non-ESC-born migrants with postgraduate degree showed significantly lower decision authority than Australia-born workers. Conclusions: This study suggests that skill discretion and job complexity but not decision authority is associated with migrant status. Migrants with high educational attainment from Non-English-speaking countries appear to be most affected by lower skill discretion/job complexity and decision authority; however, differences in skill discretion and job complexity attenuate over time for Non-ESC-born migrants, consistent with an acculturation effect. Low skill discretion and job complexity, to the extent that it overlaps with underemployment, may adversely affect migrant workers' well-being. Targeted language skill support could facilitate migrant integration into the Australian labour market.